2018
DOI: 10.1007/s10529-018-2530-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of β-glucuronidase-immobilised silica gel formulation to microfluidic platform for biotransformation of β-glucuronides

Abstract: These results revealed that usage of the microreactors has considerable potential to efficiently obtain bioactive GluA-free aglycons from various plant-derived β-glucuronides for pharmaceutical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The efficiency is equal to 1 independently from the reaction temperature, suggesting that there is no internal mass transfer limitation. This KM decrease was also reported previously [34,35]. It is assumed that better mass transfer and heat transfer in the continuous case with respect to the batch case contribute to the improvement in kinetic parameters.…”
Section: Reaction Testssupporting
confidence: 88%
“…The efficiency is equal to 1 independently from the reaction temperature, suggesting that there is no internal mass transfer limitation. This KM decrease was also reported previously [34,35]. It is assumed that better mass transfer and heat transfer in the continuous case with respect to the batch case contribute to the improvement in kinetic parameters.…”
Section: Reaction Testssupporting
confidence: 88%
“…115,116 Adding polyethylene oxide to a TEOS derived silica gel of β-glucuronidase from Helix pomatia enabled the microfluidic (the reaction was operated in small quantities of liquids within narrow channels) hydrolysis of p-nitrophenyl-β-D-glucuronide ( pNP-GluA). 117 Enzymes can be entrapped in alumina (Boehmite) gels by sol-gel processes. Liu et al claimed that hydrophilic alumina had advantages over silica, particularly, the retention of activity at high enzyme loading and the immobilization of low isoelectric point enzymes.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…An interesting example of enzyme sol-gel encapsulation for the development of a bioreactor was reported by Muderrisouglu and colleagues [69]. β-glucuronidase was immobilized into TEOS-poly ethylene oxide (PEO) derived gels.…”
Section: Enzyme Encapsulation In Silica Gels For Protein Delivery Bimentioning
confidence: 99%
“…It was found that the system was more efficient than the batch at a flux rate of 1 µL/min, but not at higher flux rate. However, the microfluidic platform maintained continuous catalytic activity for seven days [69].…”
Section: Enzyme Encapsulation In Silica Gels For Protein Delivery Bimentioning
confidence: 99%